New ways to communicate: Intensive care nurses’ perspectives on using the digital application Talk2Care. A qualitative study - Serine Ramsdal; Heidi Jerpseth (Inspira)
Background: An increasing proportion of mechanically ventilated patients are held awake or lightly sedated. These patients require advanced communication skills and sufficient time from the intensive care nurses. In recent years, different digital applications have been developed to facilitate communication with this patient group.